Study on the Relationship between Cerebral Blood Perfusion, Neuronal Cytokines and Cognitive Function in Patients with Alzheimer's Disease. - Hongjiang Lu; Yuan Fang; Xue Chen; Wendan Zhang; Yong Wang (Actas Espanolas de Psiquiatria, 2024)
Background: Alzheimer's disease (AD) is a common neurodegenerative disorder characterized by the progressive emergence of multiple cognitive deficits. Early diagnosis is of great significance for the intervention and treatment of AD. The objective of this study is to explore the relationship between cerebral blood perfusion, neuronal cytokines and cognitive function in patients with AD. Methods: AD patients admitted to the 903 Hospital of the People's Liberation Army Joint Logistics Support Force from June 2020 to January 2023 were retrospectively selected as the study objects, and 65 healthy people who underwent physical examination during the same period were included in the control group. Subjects in both groups underwent 3.0 T magnetic resonance imaging (MRI) to observe their cerebral blood perfusion parameters. The level of cognitive function in both groups was assessed using the Montreal Cognitive Assessment (MoCA). Venous blood was collected from both groups, and the serum levels of brain-derived neuronal factor (BDNF) and glial cell-derived neurotrophic factor (GDNF) were measured by enzyme-linked immunosorbent assay (ELISA). The correlation of serum BDNF and GDNF levels with cerebral blood perfusion parameters and MoCA score in the AD group was analyzed using Spearman analysis. Results: The cerebral blood flow signal intensity of the left frontal lobe, right frontal lobe, left temporal lobe, right temporal lobe, left parietal lobe, right parietal lobe, left occipital lobe, and right occipital lobe of the observation group was significantly lower than that of the control group (p<0.001). The visuospatial, executive functions, naming, attention, language function, abstract generalization ability, memory ability, orientation, and total MoCA scale scores were significantly lower than those of the control group (p < 0.001). The serum levels of BDNF and GDNF in the observation group were significantly lower than those in the control group (p<0.001). The results of Spearman analysis showed that cerebral blood perfusion parameters of the left frontal lobe, right frontal lobe, left temporal lobe, right temporal lobe, left parietal lobe, right parietal lobe, left occipital lobe, and right occipital lobe were positively correlated with cognitive function scores in AD patients, serum BDNF and GDNF levels were positively correlated with cognitive function scores in AD patients, and the correlation was statistically significant (p < 0.05). Conclusion: In AD patients, blood perfusion parameters and serum BDNF and GDNF levels were significantly lower than those of healthy people. Cerebral blood perfusion parameters of the left frontal lobe, right frontal lobe, left temporal lobe, right temporal lobe, left parietal lobe, right parietal lobe, left occipital lobe, and right occipital lobe, and BDNF and GDNF levels were positively correlated with cognitive function scores in AD patients.